Intersectional Pedagogy Creative Education Practices for Gender and Peace Work - Harmat, Gal (Taylor & Francis, 2020)
Pedagogy: Creative Education Practices for Gender and Peace Work teaches educators to use innovative learning methods to encourage students to rethink culture, gender, race, sexual orientation, and social class　 with a deep awareness of accessible language as a means of communication across disagreements. With a focus on emancipatory critical pedagogy, as well as tools to promote sustainable peace and human rights advocacy, the book's main objective is to examine and present methods that can help students address rapidly changing social situations. Recent developments under discussion include the #MeToo and #WhyIDidntReportcampaigns to counter sexual violence, campaigns to support refugees and migrants, and other human rights issues. The book examines how theory can be translated into practice and how various dilemmas pertaining to young people navigating a changing world can be successfully addressed in the classroom. This book is an ideal reading for researchers and postgraduate students in education. It is written for practitioners in peace education and for those within traditional and alternative academia who wish to promote intersectional awareness in their teaching.